A systematic review of the Limnonectes hascheanus-limborgi complex (Anura: Dicroglossidae), with the description of a new species from Peninsular Malaysia - Zou, Bei; Anuar, M.s. Shahrul; Low, Tek Joo; Hong, Zijia; Chau, Elizabeth; Grismer, L. Lee; Quah, Evan S. H. (Zootaxa, 2026)
The taxonomic confusion of the Limnonectes hascheanus-limborgi complex in Peninsular Malaysia has lasted for more than a decade since the presence of L. limborgi was reported in the country based on molecular data in 2014. Before that, L. hascheanus was thought to be the only species of L. hascheaus-limborgi complex occurring in Peninsular Malaysia. Currently, comprehensive approaches using molecular and morphological analyses corroborate the existence of a new species, Limnonectes corvus sp. nov. from Peninsular Malaysia. Limnonectes corvus sp. nov. is syntopic with L. hascheanus in some localities but differs by having an average uncorrected p-distance of 7.8% based on the 16S rRNA gene and the following diagnostic morphological characteristics: (1) small size with SVL 21.59–35.45 mm in males, SVL 28.74–35.78 mm in females; (2) short, stocky and robust body; (3) males lack external vocal sacs; (4) loreal region slightly concave; (5) tympanum approximately 2/3 of the eye diameter; (6) distinct supratympanic fold along the tympanum extending to supra-axillary region; (7) smooth skin without dense cluster of granular warts on super-axillary and cloacal region (8) fingertips with terminal bulbs; (9) relative finger lengths III>I=II>IV or III>IV=I=II; (10) inner metatarsal tubercle distinctly raised and less than 50% of the length of the first toe; (11) dermal ridge along the outer metatarsal; (12) toes basally webbed, with webbing extending to middle subarticular tubercle of the fourth toe with webbing formula as follow: I 1-–2 II 0+–22/3 III 1+–3 IV 3–11/2 V or I 1-–2 II 1+–2½ III 1½–3 IV 3–2- IV; (13) enlarged odontoids are present in both males and females. The current study found that previously reported populations of L. limborgi in Peninsular Malaysia are misidentifications of the new species L. corvus sp. nov. and we update its distribution to the east of the Bintang range to include the Sekayu lowland forest in Terengganu in the north and Ketumbar Hill, Kuala Lumpur, and Tioman Island in the south.